The characterization of a new alkaloid and other medicinal constituents of Menispermaceae with special reference to Albertisia megacarpa diels ex forman / Mohd Supi Musa - Musa, Mohd Supi (Universiti Teknologi MARA, Pahang, 1991)
Several compounds isolated from the wood of Albertisia megacarpa are identified as ∝ - amyrin, uvaol, stigmasterol and β -sitisterol. A novel azafluoranthene alkaloid isolated is given a trivial name aitidaline. The crude extract showed strong CNS avtivity on mice with LD50 253 mg/kg body weight.